Peran Literasi Keuangan Dan Perilaku Keuangan Terhadap Motivasi Entrepreneurship Mahasiswa Akuntansi - Putri Ayu Astuti; Risma Nurhapsari (MANAJEMEN, 2025)
This study aims to analyze the influence of financial literacy and financial behavior on entrepreneurial motivation among accounting students at STIE Stekom Kartasura and STEKOM University. The study sample consisted of 80 respondents obtained using the Slovin formula with a 5% margin of error. Validity and reliability tests showed that all questionnaire items were valid and reliable. The results of the classical assumption test indicated no multicollinearity, heteroscedasticity, and the data were normally distributed. Multiple linear regression analysis showed that financial literacy and financial behavior had a positive and significant effect on entrepreneurial motivation, both partially and simultaneously. The adjusted R² value of 0.648 indicates that 64.8% of the variation in entrepreneurial motivation can be explained by these two independent variables. This study emphasizes the importance of improving financial literacy and financial behavior as an effort to encourage an entrepreneurial spirit among students.